Inflammatory cascade unveiled: Exploring complications and therapeutic strategies for post-myocardial infarction inflammation (A literature review) - Bahar, Mokhamad Aswin; Prasetya, Indra (Heart Science Journal, 2024)
This comprehensive literature review delves into the inflammatory ramifications of myocardial infarction (MI), a global health concern with reported prevalences of 3.8% and 9.5% among those under and over 60 years, respectively. While the inflammatory cascade plays a crucial role in MI healing, its dysregulation can lead to complications. Recent advancements have unveiled intricate cellular and molecular pathways. The common post-MI complication of pericarditis poses diagnostic challenges due to symptom similarities with MI, requiring careful management, particularly in cases of Dressler’s syndrome. Promising therapeutic strategies, including anti-inflammatory approaches and ongoing drug development, are under exploration. Future research directions involve delving into unknown factors, identifying novel therapeutic targets, and validating emerging treatments in larger trials, emphasizing the imperative need for continued investigation into the inflammatory consequences of MI.